Sistem Negara dalam Pemikiran Ali Abdur Raziq - Abd Rahman bin Mawazi (LPPM IAIN Sorong, 2021)
The idea of ​​the state system in the Islamic intellectual realm has always been a long discussion. One of the most popular figures was Ali Abdur Raziq. He is categorized as part of a group that separates religion and state. This article aims to re-explore the archeology of knowladge on the state system in Islam as an effort to review the level of secularization in his thinking whit content analisys and philosophical approach. Ali Abdur Raziq was an influential scholar in Egypt. It became controversial when the book Islam wa Ushul al-Hukm was published. There have been many objections from scholars on the book and some have provided additional information by reconstructing their thoughts. In this study it was found that Abdur Raziq's thoughts on the state system were the result of his efforts to understand the text about the state system which according to him was not contained in the Al-Qur'an or hadith. A country with a caliphate system is a historical product that is currently developing in its time. Therefore, the present does not have to apply the caliphate system. Abdur Raziq argued that there is a need to separate religious and state affairs because religion has sacred values ​​and politics contains more profane matters. From the analysis of the contextualization of his secular thought, Abdur Raziq did not intend to separate religion and nagera with a clear dividing line, but religion remains a moral benchmark for the rulers and the state continues to take care of several things that are considered according to the mission of that religion, such as general welfare, peace. , justice as taught the prophet and apostles. Abstrak Pemikiran tentang sistem negara dalam khazanah intelektual Islam selalu menjadi permbahasan panjang. Satu di antara tokoh yang cukup populer ialah Ali Abdur Raziq. Ia kategorikan sebagai bagian dari kelompok yang memisahkan agama dan negara. Artikel ini bertujuan untuk menggali kembali arkeologi pemikirannya tentang sistem negara dalam Islam sebagai upaya meninjau tingkat sekulerisasi dalam pemikirannya menggunakan metode konten analisi dan pendekatan filosofis. Ali Abdur Raziq merupakan cendekiawan yang cukup berpengaruh di Mesir. Ia menjadi kontroversial ketika buku Islam wa Ushul al-Hukm terbit. Telah banyak sanggahan dari cendekiawan atas buku itu dan ada juga memberikan keterangan tambahan dengan merekonstruksi pemikirannya. Dalam kajian ini ditemukan bahwa pemikiran Abdur Raziq tentang sistem negara merupakan hasil upayanya memahami teks tentang sistem negara yang menurutnya tidak termaktub di dalam Al-Qur’an maupun hadis. Negara dengan sistem khilafah merupakan produk sejarah yang memang sedang berkembang di masanya. Sebab itu, masa kini tidaklah harus menerapkan sistem khilafah. Abdur Raziq berpendapat perlunya pemisahan urusan agama dan negara karena agama memiliki nilai yang sakral dan politik itu lebih banyak memuat hal profan. Dari analisa terhadap kontekstualisasi pemikiran sekulernya itu, Abdur Raziq tidaklah berniat memisahkan agama dan nagera dengan garis pemisah yang jelas, melainkan agama tetap menjadi patokan moral dalam bagi penguasa dan negara tetap mengurusi beberapa hal yang dianggap sesuai misi agama itu juga, seperti kesejahteraan umum, perdamaian, keadilan sebagaimana telah diajarkan nabi dan rasul.